Job satisfaction a research on the job satisfaction of the instructors of English at Yıldız Technical University basic english department - Kemaloğlu, Elif (My University, 2001)
Mevcut çalışma Yıldız Teknik Üniversitesi Temel İngilizce Bölümü'ndeki İngilizce öğretim görevlilerinin iş memnuniyetini özel ve genel olarak incelemek üzere yürütülmüştür. Özel incelemede iş, terfi, yönetim, çalışma arkadaşları, öğrenciler, fiziksel çalışma koşulları hakkındaki memnuniyet düzeyinin incelenmesi amaçlanmıştır. Genel incelemede ise genel iş tatmini düzeyinin sunulması ve belirlenen iş karakteristiklerine ve demografik karakteristiklere gore genel iş memnuniyeti düzeyleri arasında fark olup olmadığının araştırılması amaçlanmıştır. Memnuniyetin, iş memnuniyetinin ve

öğretimindeki iş memnuniyetinin anlamlarının analiz edildiği teorik çerçeveye dayanarak özgün bir anket geliştirilmiştir. Anket hedef grubun tümüne uygulanmıştır. Çalışmada hedef grubun memnuniyet yaratan ve memnuniyetsizliğe yol açan iş karakteristikleri belirlenmiştir. Genel iş memnuniyeti orta düzeyde, yani ne yüksek, ne de düşük bulunmuştur. Bilgisayar destekli dil öğretimi görevini üstlenen öğretim görevlilerinin diğer öğretim görevlilerine göre daha memnun olduğu saptanmıştır. Öte yandan okuma görevi üstlenen öğretim görevlilerinin diğer öğretim görevlilerine göre daha az memnun olduğu bulunmuştur. Evli öğretim görevlilerinin bekar olanlara göre daha memnun olduğu bulunmuştur. Çocuklu öğretim görevlilerinin çocuklu olmayan öğretim görevlilerine göre daha memnun olduğu ortaya koyulmuştur. Bu son iki bulgunun genel hayat memnuniyeti ve iş memnuniyeti arasında olumlu bir ilişki olduğunu ima etttiği şeklinde bir yorum yapılmıştır. ABSTRACT The present study was conducted to investigate the job satisfaction of the English instructors at Yıldız Technical University Basic English Department in specific and general terms. The objective of the specific investigation was to explore the levels of satisfaction about the work, pay, promotion, supervision, co-workers, students, physical working conditions. The objectives of the general investigation were to present the overall job satisfaction level and to investigate whether there are differences in general job satisfaction levels according to the determined work characteristics and demographic characteristics. An original questionnaire was developed on the basis of the theoretical framework in which the mening of satisfaction, the meaning of job satisfaction and the meaning of job satisfaction in English instruction were analysed. The questionnaire was applied to the entire target group. In the study, the specific job characteristics of the target group that cause satisfaction and disssatisfaction were determined. The general job satisfaction level was found to be at a medium level, i.e. neither high nor low. The instructors who assumed computer aided language teaching task have been found to be more satisfied than the other instructors whereas the instructors who assumed reading task have been found to be less satisfied than other instructors. The married instructors have been found to be more satisfied than single instructors. The instructors with children have been found to be more satisfied than the instructors without children. These last two findings were interpreted as implying a positive relationship between overall satisfaction with life and job satisfaction.
Keywords: Çalışma Hayatı Türkiye; İş Memnuniyeti